B7-H4 Inhibits the Development of Primary Sjögren’s Syndrome by Regulating Treg Differentiation in NOD/Ltj Mice - Xu Zheng; Qikai Wang; Xiang Yuan; Yingbo Zhou; Hui Chu; Guosheng Wang; Xiangpei Li; Yiping Wang; Li Wei; Li Wang; Xiaomei Li (Journal of Immunology Research)
Background. This study is aimed at exploring the role of B7-H4 in the pathogenesis of primary Sjögren’s syndrome (pSS) in NOD/Ltj mouse. Methods. B7-H4 expression in salivary glands was examined by IHC, and lymphocyte infiltration was showed by H&E. Next, anti-B7-H4 mAb or immunoglobulin isotype was injected into NOD/Ltj mice. Cytokine levels were measured by quantitative RT-PCR, and immunoglobulins were measured by ELISA. T cell subsets were analyzed by flow cytometry. Last, we treated NOD/Ltj mice with B7-H4Ig and control Ig. CD4+Foxp3+ T cells were assessed by immunohistochemistry. Two-tailed Student’s t-tests were used to detect the statistical difference in various measures between the two groups. Results. B7-H4 expression was remarkably reduced in salivary glands of NOD/Ltj mice at 15 weeks compared with the NOD/Ltj mice at 8 weeks. Anti-B7-H4 mAb treatment increased lymphocyte infiltration in salivary glands. Inflammatory cytokines including IL-12, IL-18, IL-1α, TNF-α, IFN-α, and BAFF were upregulated markedly in anti-B7-H4 mAb-treated mice compared to IgG isotype-treated mice. Flow cytometry analysis showed that anti-B7-H4 mAb-treated mice had lower levels of CD4+Foxp3+/CD4+ T cells in spleen. Moreover, Foxp3 mRNA levels of salivary glands were diminished in anti-B7-H4 mAb-treated mice. Flow cytometry analysis showed that anti-B7-H4 mAb inhibited CD4+Foxp3+/CD4+ T cell production, while B7-H4Ig would promote naïve CD4+ T into Treg differentiation. Administration with B7-H4Ig displayed significantly decreased lymphocyte infiltration in salivary glands and low levels of total IgM and IgG in serum. Analysis of inflammatory cytokines in salivary glands after B7-H4Ig treatment revealed that the mRNA levels of IL-12, IL-6, IL-18, IL-1α, TNF-α, and IFN-α were significantly downregulated in B7-H4Ig-treated mice compared to control Ig treatment. B7-H4Ig-treated mice had significantly higher levels of CD4+Foxp3+/CD4+ T cells in spleen. IHC in salivary gland revealed that CD4+Foxp3+ T cells of B7-H4Ig treatment mouse were more than control Ig treatment. Conclusions. Our findings implicate that B7-H4 has a protective role for salivary gland epithelial cells (SGECs) and therapeutic potential in the treatment of pSS.